Fly! - Teague, Mark (2019)
Mama bird wants Baby bird to learn to fly so he can migrate with the rest of the flock, but Baby bird would rather go by hot air balloon or car, instead
3-8
Keywords: Birds -- Juvenile fiction; Animals -- Infancy -- Juvenile fiction; Flight -- Juvenile fiction; Humorous stories; Picture books